Detection of virus particles and double-stranded RNA in dieback affected Dalbergia sissoo Roxb. from Bangladesh - Vogel, Stephanie; Tantau, Hanny; Mielke-Ehret, Nicole; Hoque, MI; Sarker, RH; Saha, ML; Alam, SK Shamimul; Khan, M Salim; Mühlbach, Hans-Peter (Bangladesh Journal of Botany, 2011)
Dieback of Dalbergia sissoo Roxb. (sissoo) is a disastrous disease, which has destroyed millions of forest trees in South Asia. Plant pathogenic fungi and bacteria were found associated with diseased trees, but the causative disease agent has not yet been identified unequivocally. In order to see whether plant viruses could be detected in diseased trees, present author applied bioassays, transmission electron microscopy and double-stranded RNA (dsRNA) isolation, followed by cDNA cloning. Unknown virus particles and a complex pattern of dsRNA could be detected in leaf homogenates from dieback affected sissoo trees, in contrast to an uninfected tree. Disease associated dsRNA bands ranged in size from 0.6 to 3.5 kbp, and a cDNA clone derived from dsRNA showed partial sequence homology to a plant viral RNA polymerase. Our data indicated for the first time the presence of unknown virus(es) in dieback-affected Dalbergia sissoo in Bangladesh.